Gender and obesity modify the impact of salt intake on blood pressure in children - Correia-Costa, Liane; Cosme, Dina; Nogueira-Silva, Luís; Morato, Manuela; Sousa, Teresa; Moura, Cláudia; Mota, Cláudia; Guerra, António; Albino-Teixeira, António; Areias, José Carlos; Schaefer, Franz; Lopes, Carla; et al. (Pediatric nephrology, 2016)
Most modifiable risk factors for high blood pressure (BP), such as obesity and salt intake, are imprinted in childhood and persist into adulthood. The aim of our study was to evaluate the intake of salt in children and to assess its impact on BP taking into account gender and nutritional status.
Published: 29 September 2015
Gesehen am 05.05.2020